Integrated E-Module of Local Potential Mount Merbabu to Improve High School Students Sustainable Development Goals Literacy - Nabila; Wahyudi; Sophia Tri Satyawati (Jurnal Pendidikan Indonesia, 2026)
Literacy regarding the Sustainable Development Goals (SDGs), particularly Goal 15 (Life on Land), remains relatively low due to a lack of integration of literacy into learning and a scarcity of innovative learning resources. This situation calls for the development of teaching materials that are contextual and relevant to the students’ surrounding environment. This study aims to analyze, develop, and test the validity, practicality, and effectiveness of an e-module based on local potential as a tool for SDG literacy learning. This is a development study using the 4D model (Define, Design, Develop, Disseminate) involving teachers and students as research subjects. Data were collected through interviews, questionnaires, and tests, using instruments tailored to the aspects being measured. Qualitative data were analyzed using the Miles and Huberman technique, while quantitative data were analyzed using percentage and n-gain calculations. The research results indicate that the developed e-module has a very high level of validity based on expert evaluation and is considered highly practical in its application. Furthermore, the e-module has proven effective in enhancing teachers’ pedagogical competencies, students’ interest in learning, and their literacy, with significant improvements observed in these areas. These findings indicate that integrating digitized local potential into instructional materials can serve as an effective strategy for strengthening SDG literacy. The implications of this research underscore the importance of developing innovative, locally-contextualized learning resources to support sustainable education.